User requirements for virtual reality in architectural heritage learning - Abu Bakar, Juliana Aida; Jahn Kassim, Puteri Shireen; Mahmud, Murni (Faculty of Computing, Universiti Teknologi Malaysia, 2013)
Virtual reality has inherent characteristics such as spatial navigation and presence that makes it a good candidate for learning the past. However, little is known on what are required by the experts and the general public for virtual reality, particularly, in architectural heritage learning. This article attempts to discuss user requirements from the perspective of the experts. It describes the way requirements were gathered from sequential expert interview, expert review, and expert evaluation at different stages of development. Using interviews and focus group discussions coupled with cognitive walkthrough, at least five common attributes are identified: content, support, usability, and location. This article further discusses these common attributes on user requirements and subsequently recommends potential solutions to wherever applicable.